Corporate social responsibility in sustaining water pollution a case study in Kota Kinabalu city / Alyshita Bider and Dg Seri Rahmah Abd Rahman - Bider, Alyshita (2014)
This research is about corporate social responsibility in sustaining water pollution in Kota Kinabalu city. This is a quantitative research where descriptive statistic was used to measure the degree level awareness of public servants in Kota Kinabalu city. In addition, the authors analyze the major corporate social responsibility adopted from other countries, mainly in Japan, Thailand and Korea and suggest appropriate practices for the Kota Kinabalu public sector then measure the level of awareness among the public servant in Kota Kinabalu. This study involves a total 120 respondents from various public sector, which related to environmental protection especially water. A questionnaire survey is used to obtain the research data which are later subjected to descriptive statistical analysis and frequency distribution. The result of the findings shows that the majority of the respondents were aware with water pollution. Saddest part is that, despite efforts taken by the public sector in corporate social responsibility practices, water in Kota Kinabalu continually polluted. Thus, public and private sector along with society must play a role in corporate social responsibility for sustaining water from polluted.